Optimal Method of Skin Wound Management for Total Knee Arthroplasty: A Systematic Review and Meta-Analysis - Chen, Zhongming; Bains, Sandeep S.; Sax, Oliver C.; Sodhi, Nipun; Mont, Michael A. (The Journal of Knee Surgery, 2023)
Skin closure for total knee arthroplasty (TKA) typically focuses on promoting optimal healing, while preventing wound complications and infection, allowing for functionality and immediate ambulation, and providing for excellent cosmesis. In this systematic review and meta-analysis of the literature, we will focus on closure of the skin. Specifically, we assessed: (1) wound complication risk of different techniques and (2) closing time of different sutures/techniques. There were 20 reports on infection risk and closing time. Meta-analyses focused on the qualifying studies for closing time and wound complication risk reports were also performed. These studies (378 patients) demonstrated overall lower wound complication risks with the use of barbed compared with traditional sutures (3% vs. 6%, p < 0.05). The subsequent meta-analysis included 749 patients demonstrating overall significant closing time reductions of a mean of 7 minutes with the use of barbed sutures (p < 0.05). Therefore, multiple recent reports suggest superior outcomes and faster results when using barbed sutures for TKA skin closure.
Keywords: skin; wound; closure; complications; closing time